Students’ Reflexive Ideas about Themselves as Carriers of Innovative Culture - M. N. Dudina; T. I. Grechukhina (Научный диалог)
The problem of studying reflexive ideas of University students about themselves as carriers of innovative culture in the context of dynamic socio-cultural transformations, which is little investigated in pedagogy and psychology, is considered. The novelty of the authors’ approach is to raise a question of innovative potential of the personalities of students at a University, its content and structure for the organization of targeted development of students during their studies at a University. Attention is paid to the identification of students’ ideas about the essence of the phenomenon of the carrier of innovative culture, its properties and self-awareness in this role. The results of empirical research obtained at three levels of higher education (bachelor’s, master’s, post-graduate) are presented. The comparative analysis is made of the respondents’ answers to the proposed tasks confirmed the working hypothesis about the lack of attention of theorists and practitioners of pedagogy to the problem under study. The attention is focused on the issues of necessary and timely assistance to the reflexive perception of innovations in culture. The obtained results orient teachers and managers of higher education to the organization of targeted support, facilitation of students at all levels of higher education in the field of reflexive perception of themselves as a carriers of innovative culture in conditions of increasing freedom and responsibility.